The link between regional temperature and regional incomes: econometric evidence with sub-national data. (11th February 2021) - Greßer, Christina; Meierrieks, Daniel; Stadelmann, David
Summary: We study the link between temperature and economic development at the sub-national level, employing cross-sectional data from two distinct sources. In contrast to much of the existing cross-country literature on the temperature–income relationship, our setting allows for the inclusion of country-fixed effects. Once we account for country-fixed effects, we do not find a statistically robust relationship between regional temperature and three different measures of regional economic development (per capita GDP, nightlights and gross cell production). We also test whether temperature is non-linearly related to regional income (with hotter regions being potentially particularly prone to adverse effects of temperature on income) but find no systematic evidence in favour of such a relationship. Finally, we examine whether the effect of temperature on economic development is especially pronounced in poorer regions (e.g., due to weaker adaptation). Again, we find no statistically robust link.